A Potentially Less Nephrotoxicity of Carboplatin Over Cisplatin as Radiosensitizer in Head-neck Cancer - Ahmed Riad, Mahfujul (Asian Pacific Journal of Cancer Biology, 2022)
Introduction: Head and neck cancers are the common cancers in developing countries, especially in Southeast Asia. Concurrent chemoradiation is the treatment of choice for locally advanced stage III to IVB squamous cell carcinoma of head and neck. Carboplatin can be used instead with reduced incidence of nephrotoxicity than Cisplatin. Objectives: The study has been conducted to elucidate the reduced incidence of nephrotoxicity of Carboplatin as radiosensitizing agent instead of Cisplatin. Materials and Methods: Total 60 patients were enrolled according to selection criteria among whom 30 patients received Cisplatin 40mg/m2 and Carboplatin AUC 2 along with 66Gy in 33 fractions of radiation. Every patient was evaluated routinely to see nephrotoxicity. Results: Nephrotoxicity has been assessed at routine intervals in both arms. At first week of concurrent chemoradiotherapy 8.325% and 5.825% of patients developed nephrotoxicity in arm A and B respectively. On 2nd week follow-up 25% patients of arm A and 19.175% patients of arm B developed nephrotoxicity. The p-values over the whole period of chemoradiotherapy were not statistically significant (>0.05) but arm A patient who received Cisplatin showed more incidence of nephrotoxicity than arm B who received Carboplatin. In post chemoradiotherapy follow up, 10% patients of arm A and 1.65% patients of arm B retained some sorts of renal impairment but in 4th follow up 5% patients of arm A patient retained nephrotoxicity but on the other hand none of the arm B patients had nephrotoxicity at that time. During post chemoradiotherapy period p-values between both the arms were statistically significant (<0.05). Conclusion: This study concluded that, due to low incidence of nephrotoxicity Carboplatin can be used as radiosensitizer instead of Cisplatin in locally advanced head-neck squamous cell carcinoma.